Cytomegalovirus Colitis Following Azacitidine Therapy. Issue 3 (2011) - Khan, Rajal; Rudkin, Pam; Grewal, Kuljit; Leonard, Jennifer; Hamodat, Mowafak; Hutchinson, Jim; Daley, Peter
Abstract : The present report describes the first recognized case of cytomegalovirus (CMV) colitis following azacitidine therapy. A 66-year-old woman with myelodysplastic syndrome developed CMV colitis, which responded to treatment with ganciclovir. Currently, patients receiving azacitidine do not undergo CMV testing, or receive prophylaxis or CMV-free blood products; however, this policy needs to be revised.